Islam and Eco-Theology: Perspectives and Strategies of Muhammadiyah in Addressing the Environmental Crisis - Ach. Syaiful Islam; Suhermanto Ja’far; Ahmad Sunawari Long (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2024)
This article explores the intersection of Islam and eco-theology within the context of Muhammadiyah. It is prompted by the current global environmental crisis, as the earth is facing various environmental challenges, disasters, and diseases. There is a growing awareness of the need to address these crises by drawing upon religious principles, a practice known as eco-theology. The article employs a qualitative research method using literature. Its goal is to delineate Islamic principles and eco-theology that can serve as guiding principles in natural resource management and to compare environmental theology from the perspective of the Muhammadiyah Central Environmental Council ‘Majelis Lingkungan Hidup Pimpinan Pusat Muhammadiyah’. The authors summarize the concept of Islam and eco-theology, which is based on five sharia pillars: monotheism, caliphate, trustworthiness, fairness, and istişlaḥ. Drawing from these pillars, Muhammadiyah has formulated key policies for environmental da'wah, including environmental charity (waste sadaqah), Muhammadiyah's independent environmental audit, adiwiyata (environmental care) schools, water use guidelines, environmentally friendly practices in offices, and virtual environmental da'wah and campaigns.